Tasar silkworm pupal oil: An excellent source of edible oil for industrial and therapeutic applications - Srivastava, Devika; Singh, Vandana; Ramappa, Venkatesh K. (Journal of Drug Delivery and Therapeutics, 2023)
Polyunsaturated fatty acids are widely recognized due to their remedial properties. In our previous studies, we reported that Tasar silkworm pupal oil (TSPO) is rich in polyunsaturated fatty acids, particularly alpha-linolenic acid (ALA). Further we also extracted ALA from TSPO and reported its significant anticancer activity. In the present study, extraction of TSPO and physico-chemical characterizations including saponification, acid, peroxide, iodine pH values, and colour determination were carried out to investigate the edible properties of TSPO for commercialization as a therapeutically active functional food. Further, the anti-diabetic activity of TSPO were analyzed by α-amylase inhibition assay. The saponification (154.75 ± 0.581mg KOH/g), acid (6.24 ± 0.421 mg KOH/g), peroxide (16.20 ± 0.265 meq/kg), iodine (40.33 ± 0.577g/100 ml), pH (6.17), and colour (14 Y+1.2 R) values were within the permissible range for commercialization. In addition to this, the results of the α-amylase inhibition assay showed that TSPO exhibited an IC50 value of 207339 µg/ml.  The results may facilitate the use of TSPO oil in therapeutic and functional food applicationsKeywords: Characterization; Commercialization; Tasar pupal oil; Silkworm pupae.